2013
DOI: 10.1016/j.molimm.2013.05.045
|View full text |Cite
|
Sign up to set email alerts
|

Functional analysis of a complement polymorphism (rs17611) associated with Rheumatoid Arthritis

Abstract: Complement is implicated in the pathogenesis of rheumatoid arthritis (RA); elevated levels of complement activation products have been measured in plasma, synovial fluid, and synovial tissues of patients. Complement polymorphisms are associated with RA in genome-wide association studies. Coding-region polymorphisms may directly impact protein activity; indeed, we have shown that complement polymorphisms affecting a single amino acid change cause subtle changes in individual component function that in combinati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Purification of C5 has been challenging; early methods were laborious and inefficient with a very low recovery of active C5 . Current affinity purification methods are faster but are complicated by low yield (> 50%) and poor functional activity of the protein, a consequence of its pH lability and tendency to associate with C6 if denatured . Here we took advantage of a recently described anti‐C5 therapeutic mAb, RO7112689, that was selected to recycle in vivo by shedding its cargo when exposed to acidic pH (~ pH5·5) in the endosome .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Purification of C5 has been challenging; early methods were laborious and inefficient with a very low recovery of active C5 . Current affinity purification methods are faster but are complicated by low yield (> 50%) and poor functional activity of the protein, a consequence of its pH lability and tendency to associate with C6 if denatured . Here we took advantage of a recently described anti‐C5 therapeutic mAb, RO7112689, that was selected to recycle in vivo by shedding its cargo when exposed to acidic pH (~ pH5·5) in the endosome .…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8][9] Current affinity purification methods are faster but are complicated by low yield (> 50%) and poor functional activity of the protein, a consequence of its pH lability and tendency to associate with C6 if denatured. [10][11][12] Here we took advantage of a recently described anti-C5 therapeutic mAb, RO7112689, that was selected to recycle in vivo by shedding its cargo when exposed to acidic pH (~pH5Á5) in the endosome. 13 Such antibodies have been engineered to reduce therapeutic dose; 16,17 pH-dependence to release soluble antigen in the endosome is an essential property.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…C5a(desArg), C3a(desArg), factor D and properdin were quantified using their respective commercial assays from Hycult Biotech, as instructed by the manufacturer. Plasma C5, TCC and factor H were all measured using in‐house ELISA 24‐26 . All assays used purified protein (either C5, TCC or factor H) as a standard.…”
Section: Methodsmentioning
confidence: 99%
“…Meanwhile, study by Chai L et al, also reported that rs17611 was associated with periodontitis [30]. Furthermore, functional analysis on rs17611 showed that individuals homozygously expressing the risk allele G exhibit increased C5a and decreased C5 in plasma, which potentially explain the genetic association of C5 rs17611 with uveitis [31].…”
Section: Discussionmentioning
confidence: 96%